2017
DOI: 10.5455/ajvs.262147
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile of Drinking Water of Broiler Farms in Beheira Province

Abstract: Key words:Water, Chemical examination, Broiler farmsIn order to have a clear picture for chemical quality of drinking water used in some broiler farms, a total of 100 water samples were collected (each sample represents a farm); 56 samples from underground water and 44 from tap water. Samples were collected from broiler farms in different localities of Beheira Province during the period from July 2015 to June 2016. Chemical analysis was performed at the laboratory of Department of Veterinary Hygiene and Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…TDS levels over 3,000 mg/L can cause diarrhea, reduce economic performance, and raise chicken death rates (Sumano et al, 2004). TDS were not closely associated with poultry health concerns, but they might negatively impair equipment efficiency and water supply, influencing bird performance Ayoub et al, 2017). groundwater samples in Kalyobia governorate, Egypt was below the allowed level of WHO (200 mg/L) for chloride.…”
Section: Tds (Total Dissolved Solids)mentioning
confidence: 99%
See 4 more Smart Citations
“…TDS levels over 3,000 mg/L can cause diarrhea, reduce economic performance, and raise chicken death rates (Sumano et al, 2004). TDS were not closely associated with poultry health concerns, but they might negatively impair equipment efficiency and water supply, influencing bird performance Ayoub et al, 2017). groundwater samples in Kalyobia governorate, Egypt was below the allowed level of WHO (200 mg/L) for chloride.…”
Section: Tds (Total Dissolved Solids)mentioning
confidence: 99%
“…It was shown that excessive chloride levels could lead to metabolic disturbances (Coetzee et al, 2000). High chloride levels increase water intake, reduce feed consumption, and have a digestive impact (Ayoub et al, 2017).…”
Section: Tds (Total Dissolved Solids)mentioning
confidence: 99%
See 3 more Smart Citations